Effects of Bifidobacterium animalis ssp. lactis 420 on gastrointestinal inflammation induced by a nonsteroidal anti‐inflammatory drug: A randomized, placebo‐controlled, double‐blind clinical trial. Issue 12 (30th May 2021) - Mäkelä, Sanna M.; Forssten, Sofia D.; Kailajärvi, Marita; Langén, Ville L.; Scheinin, Mika; Tiihonen, Kirsti; Ouwehand, Arthur C.
Abstract : Aims: Use of nonsteroidal anti‐inflammatory drugs (NSAIDs) can cause damage to the gastric and duodenal mucosa. Some probiotics have proven useful in ameliorating the harmful side‐effects of NSAIDs. Our aim was to evaluate whether oral administration of Bifidobacterium animalis ssp. lactis 420 (B420) can attenuate the increase of calprotectin excretion into faeces induced by intake of diclofenac sustained‐release tablets. Methods: A double‐blind, parallel‐group, placebo‐controlled and randomized clinical study was performed in 50 healthy male and female volunteers aged 20–40 years, in Finland. Study participation consisted of 4 phases: run‐in, intervention with B420 or placebo, B420 or placebo + NSAID treatment, and follow‐up. The primary outcome was the concentration of calprotectin in faeces. Secondary outcomes were haemoglobin and microbial DNA in faeces and blood haemoglobin levels. Results: Intake of diclofenac increased the faecal excretion of calprotectin in both groups. The observed increases were 48.19 ± 61.55 μg/g faeces (mean ± standard deviation) in the B420 group and 31.30 ± 39.56 μg/g in the placebo group (difference estimate 16.90; 95% confidence interval: −14.00, 47.77; P  = .276). There were no significant differences between the treatment groups in changes of faecal or blood haemoglobin. Faecal B. lactis DNA was much more abundant in the B420 group compared to the placebo group (ANOVA estimate for treatment difference 0.85 × 10 9 /g faeces; 95% confidence interval: 0.50 × 10 9, 1.21 × 10 9 ; P  < .0001). Conclusions: Short‐term administration of the probiotic B420 did not protect the healthy adult study participants from diclofenac‐induced gastrointestinal inflammation as determined by analysis of faecal calprotectin levels.